THE USE OF DRILLING TECHNIQUE IN TEACHING ENGLISH VOCABULARY TO EIGHTH GRADE STUDENTS - Ariska Puteri, - (2022)
The limited of vocabulary is the major difficulty factor in English language learning. One of the ways to solve this difficulty is by using the technique for teaching English such as the use of drilling techniques. Therefore, the present study focused on the investigation of the use of drilling techniques in teaching English vocabulary to eighth-grade students in one junior high school in Bandung. The purpose of this study is to find out whether or not the use of drilling technique is effective to improve students' vocabulary. Also, it intends to see the students' responses to the use of drilling techniques in teaching English vocabulary. The research design used in this study is the quasi-experimental design involving sixty students in eighth grade (8.7 and 8.8) at one public junior high school in Bandung. The data were collected from pretest, post-test, and questionnaire. The findings from the pretest and post-test were analyzed by using an independent t-test. It shows the mean for the experimental group is 71.20 and the mean for the control group is 68.53. The t-test result was 0.042 which is lower than the alpha level (0.042<0.05). It means there is a significant difference in students' vocabulary after applying the drilling techniques. Furthermore, the r-value was 0.218, which indicates the drilling technique associated with students' vocabulary at a small level. The questionnaire result indicates that the students have positive responses to the use of drilling techniques. It shows by the fact that most of the students get the benefits from using drilling techniques such as enriching their English vocabulary. As a result, it can be concluded that the use of the drilling technique is effective in improving students' vocabulary. Keywords: drilling technique, teaching English, vocabulary